PERALIHAN HAK TANAH DENGAN MENGGUNAKAN AKTA KUASA MUTLAK SEBAGAI TINDAK LANJUT PERJANJIAN PENGIKATAN JUAL BELI TANAH - Yosita Erva Yanti; Agus Trisaka (Universitas Sriwijaya, 2023)
Transfer of Land Rights Using Deed of Absolute Power of Attorney as a Follow-up to the Agreement on Sale and Purchase of Land is an absolute power of attorney allowed as a follow-up to the binding agreement of sale and purchase (ppjb), where the making of a deed of binding agreement of sale and purchase (ppjb) as a preliminary agreement in the presence of a notary with the aim of providing protection for the parties so that the prospective seller does not transfer the object of sale and purchase to another party and the prospective buyer does not cancel the sale and purchase agreement to be made between the two. Of course, as a Notary, you must be careful not to let the prospective buyer be a foreign national. The absolute power of attorney received by the buyer from the seller is to be able to act alone to go through the next process, for example turning the name before the PPAT. Legal protection of Notary in the making of absolute power of attorney deed as a follow-up to the agreement of binding sale and purchase (PPJB) of land rights has been in accordance with the laws and regulations and the code of ethics of Notary. Settlement of legal disputes in the PPJB of land rights using absolute power of attorney deed as a follow-up to the agreement of binding sale and purchase (PPJB) of land rights is by deliberation and court. Dispute resolution in the deed if generally resolved in the Court in the city concerned, but if it is not too complicated, it is resolved by deliberation.Keywords: Transfer of Rights, Deed of Absolute Power of Attorney, Sales and Purchase Agreement